Fundamental determinants of exchange rate expectations - Joscha Beckmann; Robert L. Czudaj (ZBW - Leibniz Information Centre for Economics, 2020)
This paper provides a new perspective on the exchange rate disconnect puzzle by referring to the expectations building mechanism in foreign exchange markets. Therefore, we analyze the role of expectations regarding macroeconomic fundamentals for expected exchange rate changes. In doing so, we assess data for 31 economies from 2002 to 2017 and consider expectations regarding GDP growth, in ation, interest rates and current accounts. Our empirical findings identify an impact of expected fundamentals, which is not fully consistent with traditional fundamentals models. We especially highlight the relevance of the PPP theory for the expectations building mechanism due to the robust finding that in ation expectations are able to explain expected exchange rate changes in line with the purchasing power parity. We also find that the expectation building process differs remarkably between the periods prior and after the global financial crisis since the impact of GDP growth expectations clearly disappears for the second subsample period, which can be explained by the scapegoat approach. Finally, we also find that in ation expectations affect both the dispersion across forecasters and realized forecast errors.
Keywords: F31; F37; G17; 330; Disagreement; Exchange rates; Expectations; Forecast errors; Fundamentals; Survey data